The interaction of job resources and organizational identification in predicting employee's well-being - Tavares, S. M. (12th EAOHP Conference (“Occupational health psychology in times of change: society and the workplace”)., 2016)
The idea that job resources lead to increased well-being became increasingly popular among researchers. In fact, in organizational settings, several empirical studies have evidenced that when people perceive higher levels of job resources they report increased levels of well-being. However, the present work questions this assumption. Is job resources' impact on well-being always positive? Are job resources always resourceful? In fact, based on the Conservation of Resources Theory (Hobfoll, 1989; 2002), we propose that employees' perception of job resources and their level of organizational identification (OI) interact in predicting employees' well-being; in that when OI is higher, job resources will play a more significant role in predicting well-being. In order to test this general hypothesis, we performed 3 studies based on crosssectional surveys applied to the employees of 3 different organizational settings: lawyers (N=106), cleaning employees (N= 145) and employees from an aviation firm (N= 72, in a two wave study). In these 3 studies we analysed the interaction of organizational identification and different job resources (perceived organizational support (study 1), interactional justice (study 2), and psychological empowerment (study 3) in the prediction of important aspects of employees' well-being: work engagement (study 1), life satisfaction (study 2), and pleasant affect at work and sleep quality (study 3). Results are largely consistent across the three samples and show that the benefit of these job resources for employees' well-being is contingent on the degree of their perceived oneness with the organization. In other words, the relationship between these job resources and employees' well-being is moderated by OI, so that these job resources only have positive impact on employees' well-being when OI is high. These results speak to the added value of integrating organizational identification in understanding the impact of job resources on employees' well-being. Implications and suggestions for future studies on the relationship between job resources and well-being are discussed.